Perspektif Hukum Adat Bali Mengenai Waris Dalam Perkawinan Pada Gelahang Dan Upaya Penyelesaian Sengketa Warisnya - Sathya, Putu Karunia Sai; Zubaedah, Rahmi (Jurnal Ilmiah Wahana Pendidikan, 2025)
Balinese customary law, which is patrilineal in nature, causes problems for families who are limited in having sons and threatens to break the lineage and break inheritance in the family. Therefore, an alternative marriage was born which is called bilateral gelahang marriage. The differences between the family system used in Balinese customary law and the marriage system in the gelahang, give rise to several problems and solutions to these problems are needed with protection for families who carry out marriages in the gelahang, therefore this journal will discuss this phenomenon.